Banking liquidity regulation: Impact on their business model and on entrepreneurial finance in Europe1. (24th August 2018) - Paulet, Elisabeth
Abstract : Banking liquidity regulation has transformed banks' business model and hampered entrepreneurial finance by reducing credit distribution. If capitalization and liquidity ratio have induced more stability, they have reduced the margin and profitability of European financial institutions. This fact has influenced the financing of enterprises in general and small and medium sized enterprises in particular. Hence, firms were obliged to find other sources of financing to undertake their projects and have contributed to transforming the business model of banking institutions.